Mapping and Identification of Mangrove in Coastal Area of Wongsorejo District - Shinta Hiflina Yuniari (Journal of Aquaculture Science, 2021)
The northern to southern of Banyuwangi there have the stretches of mangrove, nevertheless  only a few of mangrove locations have been identified and mapped based the type and extent of the mangroves. The coastal area of Banyuwangi Regency is the longest in East Java, with mangrove as the priority of tourism program coastal resources, therefore must be conservated. This study aims to determine the types of mangroves on Wongsorejo coastal, mapping  the distribution of mangroves on Wongsorejo coastal, and determine the diversity of mangroves on Wongsorejo coastal. The research design used in this research is descriptive quantitative. Methods of data analysis using spatial analysis and analysis of mangrove vegetation. The results showed that there were 18 mangrove species consisting of 10 true mangroves and the remaining 8 associated mangroves, such as Avicennia lanata, Avecennia marina, Sonneratia alba, Rhizophora apiculata, Avicennia alba, Rhizophora stylosa, Rhizopora mucronata, Excoearia agallocha L, Lumnitzera racemose, Willd. var. Racemosa, Phemphis acidula, Wedelia biflora, Ipomoea pes-caprae, Calontropic gigantea, Clerodendrum inerme Gaertn, Hibiscus tiliaceus L, Morinda citrifolia L, Passiflora foetida, Sesuvium portulacastrum. The relative density of mangroves on Wongsorejo coastal was less than 50%, which means that mangroves are few/rare and/or in heavily damaged condition. Meanwhile, diversity based on the analysis carried out shows moderate diversity. Keyword : Identification, Mapping, Mangrove, Wongsorejo Coastal.